TORAKOCHIRURGIAClassification of laryngotracheal stenosis - Wierzbicka, Małgorzata; Szyfter, Witold; Popko, Mariola (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduction: Laryngotracheal stenosis (LTS) is a relatively rare disease. Careful diagnostics and classification are essential for planning the following treatment and assessing its results. To classify LTS, endoscopic and imaging techniques are required. Aim: To discuss different systems of LTS classifications based on a literature review and our clinical experience. Also, to propose the best classification for Polish ENT and thoracosurgery departments. Material and Methods: A retrospective review of 124 patients treated for LTS between January 1999 and December 2008 has been completed. The following variables have been analyzed: age, gender, cause of stenosis, and outcome. Results: Out of 124 LTS patients, 118 had prolonged intubation or high tracheotomy, 3 Wegener’s granulomatosis, 1 Riedel’s goitre, 1 Schimmelpennig-Feuerstein-Mims disease and 1 Still disease. Localization of the stenosis was as follows: glottic-subglottic in 77, subglottic in 17 and tracheal in 35 patients. The stenoses were assessed as stage I in 5 patients, stage II in 37, stage III in 45 and stage IV in 37 patients in the Cotton grading system. Conclusions: The use of complex grading systems is unrealistic in everyday work by Polish ENT surgeons and thoracosurgeons. We suggest implementing the Cotton system and Medical Research Council dyspnoea scale as the optimal way to classify and assess the outcomes of LTS treatment. The former system is well known and widely advocated in Poland, the latter requires a modicum of time from the physician. Both scales, as a combination of subjective and objective parameters, show a strong correlation and therefore complement each other.